Purification and Structural Characterization of a Novel Water-Soluble Neutral Polysaccharide from Cantharellus cibarius and Its Immunostimulating Activity in RAW264.7 Cells - Long Chen; Xichun Peng; Jiaying Lv; Siyin Liao; Shiyi Ou; Yingbin Shen (International Journal of Polymer Science)
Polysaccharide is one of the important active ingredients of Cantharellus cibarius. The aims of this work were to analyze preliminary characterization and to investigate immunostimulating activity of a novel water-soluble neutral polysaccharide named JP1, which was purified from the fruiting body of Cantharellus cibarius using DEAE-FF chromatography and Sephadex G-100 chromatography. The characteristics of JP1 were determined by HPGPC, FT-IR spectra, gas chromatography, and Congo Red Method. Immunostimulating activity of JP1 was investigated in RAW264.7 cells. Results indicated that JP1 consisted of L-Arabinose, D-Mannose, D-Glucose, and D-Galactose in a molar ratio of 1 : 1.06 : 1.95 : 1.17 with a molecular weight of 336 kDa. JP1 is nontoxic to RAW264.7 cells at this concentration range (62.5–1000 μg/mL). Furthermore, JP1 can promote mouse peritoneal macrophages to secrete NO and enhance the secretion of macrophages’ cytokines IL-6 in RAW264.7 cells. These results suggested that JP1 could have potential immunostimulating activity applications as medicine or functional food.